HU Overview of Conservation Tillage Practices for Developing and Sustaining Climate Change Resilient Soils in Sub-saharan Africa - Modiba, Maimela Maxwell; Hanaa Tharwat, Mohamed Ibrahim; Dekemati, Igor; Simon, Barbara (Journal of Central European Green Innovation, 2023)
Change in hydrological intensity in the form of rainfall is predicted to worsen in Southern Africa. Compounded by consequences of higher global temperatures such as heatwaves, may render many Southern African regions prone to drought. The agricultural sectors of the latter regions are faced with a greater threat. In view of such concerns, the aim of this study is to review the available literature to evaluate climate-smart agricultural practices suitable for the mitigation of climate change challenges faced by farmers. Climate-smart agriculture practices are advocated as alternatives for mitigating and managing climate change problems, increasing food production, and improving rural people's livelihoods. This review paper is aimed at the bestowed benefits of climate-smart agricultural practices on soil physical, chemical, and biological and its association to mitigate or manage predicted climate change effects in SSA.
Keywords: CA (Conservation Agriculture); Tillage; Sub-Saharan Africa (SSA); Climate change; Climate-smart agriculture (CSA)